2017
DOI: 10.1177/0143831x17738041
|View full text |Cite
|
Sign up to set email alerts
|

Voice through exit: Changing working conditions by independent contractors’ participation

Abstract: In the course of worldwide reforms in health care systems, flexible employment is of increasing relevance in medicine and also includes the highly skilled workforce of hospital physicians. With reference to Hirschman’s seminal work on exit, voice and loyalty, this article analyzes the phenomenon of deploying locum tenens physicians as independent contractors in hospitals. The results of two qualitative empirical studies drawing on 30 qualitative interviews show conditions and consequences of exit– voice– loyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…They argued that both workers in TERs and NTERs are less likely to display a reasonable degree level of influence in management decisions and actions. Surprisingly, Ruiner et al (2020) found independent consultants in the health sector having a higher degree of influence than permanent physicians. They argued that the independent consultants could influence management actions by voicing due to expertise, freedom, and loyalty to professional values.…”
Section: Employee Voice Influencementioning
confidence: 95%
See 4 more Smart Citations
“…They argued that both workers in TERs and NTERs are less likely to display a reasonable degree level of influence in management decisions and actions. Surprisingly, Ruiner et al (2020) found independent consultants in the health sector having a higher degree of influence than permanent physicians. They argued that the independent consultants could influence management actions by voicing due to expertise, freedom, and loyalty to professional values.…”
Section: Employee Voice Influencementioning
confidence: 95%
“…Direct voice was the most common form of voice among non-traditional workers (see Goñi-Legaz & Ollo-López, 2017;McDonnell et al, 2014). Among professionals in disguised or dependent self-employment, an informal pattern of worker participation was reported (Ruiner et al, 2020). Daily walk-around conversations, in-depth conversations between individual employees and managers, suggestion schemes, electronic mails, staff surveys, social networking sites, installed support software are the direct forms of voice reported (see Gegenhuber et al, 2021;Good & Cooper, 2014).…”
Section: Forms Of Employee Voicementioning
confidence: 99%
See 3 more Smart Citations